2020
DOI: 10.18388/abp.2020_5402
|View full text |Cite
|
Sign up to set email alerts
|

C-C motif chemokine ligand 5 and C-C chemokine receptor type 5: possible diagnostic application in breast cancer patients

Abstract: The chemokine CCL5 and its receptor CCR5 play important roles in cancer invasion and metastasis. Based on our knowledge, our results were the first that presented the diagnostic usefulness of CCL5 and CCR5 in breast cancer (BC) patients, based on receiver operating characteristic (ROC) curve analysis. We wished to examine further if CCL5 and CCR5 are appropriate to be applied as BC markers for early screening. Values of tested parameters in patients’ plasma were determined by CMIA method (Chemiluminescent Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Research has shown that CCR5 expression is elevated in lung cancer cells and is associated with increased tumor invasiveness and metastasis. Interaction between CCR5 and its ligands can promote cancer cell migration, invasion, and resistance to apoptosis [51][52][53]. ACE (Angiotensinconverting enzyme): ACE is an enzyme that plays a crucial role in the renin-angiotensin system, which regulates blood pressure and fuid balance.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that CCR5 expression is elevated in lung cancer cells and is associated with increased tumor invasiveness and metastasis. Interaction between CCR5 and its ligands can promote cancer cell migration, invasion, and resistance to apoptosis [51][52][53]. ACE (Angiotensinconverting enzyme): ACE is an enzyme that plays a crucial role in the renin-angiotensin system, which regulates blood pressure and fuid balance.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 and its ligands, particularly CCL5 have been thought to support tumor growth either directly, by driving the migration of tumor cells to tumor sites, and mostly by recruiting MDSC and dendritic cells to the tumor site [ 96 , 97 , 98 , 99 , 100 ]. Many studies showed a clear link between CCR5 and CCR5 ligands polymorphism or differential gene signature and several cancer diseases, among them: prostate cancer, breast cancer, glioblastoma, myeloid leukemia, pancreatic adenocarcinoma, Non-Small Cell Lung Cancer (NSCLC), metastatic melanoma, metastatic colorectal cancer and others [ 98 , 99 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ]. Following Balistreri et al [ 129 ] that observed a very low prevalence of prostate cancer in men with CCR5 delta 32 mutations, which also confers HIV resistance, we have used mice lacking CCR5 to uncover the contribution of CCR5 to the cancer resistance and found that in these mice accumulation of MDSC at the tumor site is inadequate [ 130 ].…”
Section: Key Chemokine-chemokine Receptor Interactions That Support Tumor Growthmentioning
confidence: 99%
“… 3 , 6 New candidates being considered as potential BC markers include matrix metalloproteinases, 7 cytokines 8 and also chemokines. 9 …”
Section: Introductionmentioning
confidence: 99%
“…3,6 New candidates being considered as potential BC markers include matrix metalloproteinases, 7 cytokines 8 and also chemokines. 9 The pathogenesis of BC is a complex process, related to the patient's age, genetic, hormonal and environmental factors. 3,4,10 Among the most recent factors associated with an increased risk of BC is chronic inflammation -associated with both cancer formation and progression.…”
Section: Introductionmentioning
confidence: 99%